Grasping the paradoxical nature of wisdom through unconscious integrative complexity - Kam, Christopher; Bellehumeur, Christian R. (Frontiers in Psychology, 2022)
There has been much progress in the scientific study of wisdom on both conceptual and empirical fronts in the past few decades. Despite all the progress being made, there are still gaps that can be filled to provide even more explanatory power and coherence. Although academic discourse on the nature of wisdom has included the ability to integrate issues in a complex manner, there is still room for improved theorizing on wisdom’s integrative complexity. Since integrative complexity has both conscious and unconscious dimensions, including the latter in discussions on wisdom will add a valuable aspect to its conceptualization. This article will argue how unconscious integrative complexity is the variable in wisdom’s conceptual equation that involves paradox, which is a well known sign of wisdom. Explanations contrasting conscious integrative complexity and unconscious integrative complexity in reference to wisdom will be discussed. Then, the Archetypal Test of the Nine Elements will be proposed as a testing instrument to operationalize unconscious integrative complexity. After the conceptualization and operationalization are worked through, we will conclude with a couple examples to illustrate our reflections.